Hubungan Pengetahuan Makanan Sumber Fe Dan Vitamin C Dengan Kadar Hb Pada Ibu Hamil Post Hiperemesis Gravidarum di Rumah Bersalin Budi Rahayu Semarang - Amaliyah -; Sufiati Bintanah; Siti Aminah (Jurnal Gizi, 2014)
Anemia can be caused by several factors, including the lack of intake of Fe and mother's knowledge. Anemia can occur at any age, especially in pregnant women. Pregnant women are prone to anemia compared with women who did not become pregnant because of the needs of pregnant women Fe higher than non-pregnant women (Widiyanto, 2001). For that pregnant women should pay attention to food intake during pregnancy progresses. The purpose of the study is to determine the relationship of Fe and knowledge of food sources of vitamin C with hemoglobin levels in pregnant women with hyperemesis gravidarum post. The research method sectional survey approach (cross sectional) in the field of clinical nutrition. The population is all pregnant women in the maternity hospital Budi Rahayu who come and check her pregnancy in the maternity hospital Budi Rahayu in June-July 2011 as many as 30 people. Samples were taken by purposive criteria: outpatients at the maternity hospital Budi Rahayu, willing to be a sample and follow up completed research, pregnant women with hyperemesis gravidarum post. Univariate analysis was used to determine the frequency distribution of the sample characteristics and bivariate to know know the relationship between two variables, preceded by a Kolmogorov-Smirnov test to determine normality test data and proceed to the Spearman Rank correlation test. The characteristics of pregnant women with hyperemesis gravidarum post, 86.6% aged 20-30, years, 66.7% had high school, 80% were knowledgeable, 56.7% work as private employees, 30.0% Fe knowledge of food sources moderate, 40.0% knowledge of good food sources of vitamin C, 83.3% of pregnant women pengalami anemia. Normality test indicates that the data are not normally distributed, p-value 0.002 (<0.05) so using Spearman rank correlation test. Results of bivariate analysis showed that there was no relationship between fe and knowledge of food sources of vitamin C with hb levels in pregnant women with hyperemesis gravidarum post maternity home rahayu Semarang favor with the value of r = 0.305 and p = 1.000 (<0.05).